Preventing Meningococcal Disease in US Adolescents and Young Adults Through Vaccination - Jessica Presa; Ruth Carrico; Jaime E. Fergie; Stephanie Hanenberg; Gary S. Marshall; Kaitlyn Rivard; Jana Shaw; Gregory D. Zimet; Paula Peyrani; Alejandro Cane (Infectious Diseases and Therapy)
Abstract In 2022, experts convened under the name Advancing Strategies to Prevent Meningococcal Disease (ARTEMIS) to gather insights on issues related to invasive meningococcal disease (IMD) and meningococcal vaccination in the US. Discussions regarding successes, challenges, and future directions for the US meningococcal vaccination program are summarized. Current vaccination recommendations target adolescents/young adults (AYA), who are at increased risk of IMD. Suboptimal vaccination rates, particularly for meningococcal serogroup B disease, may stem from gaps in knowledge surrounding IMD and meningococcal vaccination among healthcare providers (HCPs), parents, and AYA; confusion among HCPs regarding the shared clinical decision-making recommendation for serogroup B vaccinations; demographic variables; and lack of preventive healthcare visits. ARTEMIS proposed strategies to address knowledge gaps and access barriers at the HCP, parent/AYA, and educational institution/policymaker levels. Alternative vaccination schedules using a recently approved MenABCWY vaccine that provides protection against all five major serogroups may simplify meningococcal vaccination and increase coverage.